Analysis of the Influence of the Tourism Industry Sector on Local Original Income in Karo Regency in 2018-2023 - Nadila Huswatun Hasanah; Ahmad Fadlan; Rahmad Sembiring (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
The purpose of this study is to examine how the number of visitors to Karo Regency and the number of tourist attractions impact Regional Original Income (PAD) in Karo Regency during the 2018–2023 period. The secondary data used in this study was obtained from the Central Statistics Agency (BPS) and the Karo Regency Tourism Office. To determine the influence of the independent variables on the dependent variable, both partially and simultaneously, descriptive analysis and multiple linear regression were employed. The results indicate that the number of tourist attractions and the number of tourists have a significant simultaneous effect on PAD, with a coefficient of determination (R²) of 0.85, meaning that these two variables account for 85% of the variation in PAD. The number of tourist attractions has a significant partial effect on PAD, whereas the number of tourists does not. In addition to providing theoretical insights into the relationship between tourism and PAD, this study offers practical benefits in the form of strategic recommendations for tourism management in Karo Regency. However, the study is limited to data collected within a specific period and does not include additional variables such as hotel occupancy rates or tourist spending. Future research is expected to incorporate more variables and a broader dataset to provide a more comprehensive understanding of the topic.